Effects of Nonlinear Aerobic Training on Erectile Dysfunction and Cardiovascular Function Following Radical Prostatectomy for Clinically Localized Prostate Cancer - Jones, Lee W. (2013)
Erectile dysfunction (ED) is a major adverse effect of radical prostatectomy (RP). We conducted a randomized controlled trial to examine the efficacy of aerobic training (AT) compared with usual care (UC) on ED prevalence in 50 men (n = 25 per group) after RP. AT consisted of five walking sessions per week at 55– 100% of peak oxygen uptake (VO(2peak)) for 30–60 min per session following a nonlinear prescription. The primary outcome was change in the prevalence of ED, as measured by the International Index of Erectile Function (IIEF), from baseline to 6 mo. Secondary outcomes were brachial artery flow–mediated dilation (FMD), VO(2peak), cardiovascular (CV) risk profile (eg, lipid profile, body composition), and patient-reported outcomes (PROs). The prevalence of ED (IIEF score ≤21) decreased by 20% in the AT group and by 24% in the UC group (difference: p = 0.406). There were no significant between-group differences in any erectile function subscale (p > 0.05). Significant between-group differences were observed for changes in FMD and VO(2peak), favoring AT. There were no group differences in other markers of CV risk profile or PROs. In summary, nonlinear AT does not improve ED in men with localized prostate cancer in the acute period following RP.